Sweet corn seeds treatment and deterioration under modified atmosphere - Pereira, Cristiane Carvalho (2021)
Sweet corn seeds have high sugar content in the endosperm, to the detriment of starch, this characteristic makes the seeds more susceptible to pests and diseases, and causes low germination and vigor. Seed treatment is an extremely important alternative to ensure the development of seedlings in the initial phase, avoiding damages caused by pests and diseases and, positively affecting the productive potential of the crop. However, some products can cause phytotoxicity when applied in advance of sowing, and this effect can worsen over the storage period. Among the factors that influence the physiological quality of seeds during storage, relative humidity, temperature and the presence of oxygen are considered fundamental factors for seed conservation. Oxygen- restricted conditions prolong seed longevity during storage, however, relative humidity and storage temperature in airtight conditions are important, since high temperatures and relative humidity can intensify respiration processes. In this context, two studies were carried out with the aim of investigating the effect of storage conditions on the deterioration of sweet corn seeds. In the first study, sweet corn seeds were subjected to seed treatment using three different mixtures of fungicide and insecticides, Metalaxil-M + Fludioxonil (M), Metalaxil-M + Fludioxonil + Clotianidina (MP) and Metalaxil-M + Fludioxonil + Clotianidina + Clorantraniliprole (MPD), and stored for one year in a cold chamber with vacuum plastic and paper packaging. The evaluation of the physiological and sanitary quality of the seeds was carried out before the beginning of storage, at four and twelve months, through germination, cold test, accelerated aging, hypocotyl dry mass, emergence speed index, seedling emergence and seed health test. The use of insecticides such as Clotianidin + Chlorantraniliprole, negatively affects the vigor of sweet corn seeds during storage for one year at a temperature of 10 o C. The type of packaging and treatment with insecticides Clotianidin + Clorantraniliprole, associated with the fungicide Metalaxyl-M + Fludioxonil, affect the fungal incidence of stored sweet corn seeds. Vacuum packaging provides greater longevity and maintenance of the physiological and sanitary quality of sweet corn seeds during storage in a cold chamber, when compared to paper packaging. In the second study, sweet corn and waxy corn seeds were used to construct sorption and desorption isotherms and to evaluate oxygen consumption, carbon dioxide and ethanol production during storage in airtight packaging. In addition, sweet corn seeds were stored for eighteen months under different conditions of relative humidity (30, 45 and 60%), temperature (20 and 30 o C) and oxygen concentrations (1, 5, 10, 21, 50 and 99%), and evaluated by measuring oxygen consumption, carbon dioxide and ethanol production and through the germination test after six and eighteen months of storage. The storage of sweet and waxy corn seeds under oxygen-restricted conditions with water activity levels above 0.7 causes anaerobic respiration and accelerates seed deterioration processes. Sweet corn seeds have a greater longevity when stored under conditions of 30% relative humidity and oxygen contents of 1% to 10%, at a temperature of 30 o C. However, when stored at a temperature of 20 o C, only a reduction in relative humidity to 30% or 45% is enough to prolong the longevity of sweet corn seeds.